Relation Between Working Memory Capacity of Biological Movements and Fluid Intelligence - Ye, Tian; Li, Peng; Zhang, Qiong; Gu, Quan; Lu, Xiqian; Gao, Zaifeng; Shen, Mowei (Frontiers in Psychology, 2019)
Studies have revealed that there is an independent buffer for holding biological movements (BM) in working memory (WM), and this BM-WM has a unique link to our social ability. However, it remains unknown as to whether the BM-WM also correlates to our cognitive abilities, such as fluid intelligence (Gf). Since BM processing has been considered as a hallmark of social cognition, which distinguishes from canonical cognitive abilities in many ways, it has been hypothesized that only canonical object-WM (e.g., memorizing color patches), but not BM-WM, emerges to have an intimate relation with Gf. We tested this prediction by measuring the relationship between WM capacity of BM and Gf. With two Gf measurements, we consistently found moderate correlations between BM-WM capacity and the score of both Raven’s Advanced Progressive Matrix (RAPM) and the Cattell Culture Fair Intelligence Test (CCFIT). This result for the first time revealed a close relation between WM and fluid intelligence with a social stimulus and challenged the double-dissociation hypothesis for distinct functions of different WM buffers.